Where There's Fire, There's Smoke: Air Quality and Prescribed Burning in Florida - Martha C. Monroe; Adam C. Watts; Leda N. Kobziar (EDIS)
Revised! FOR-62, a 5-page illustrated fact sheet by Martha C. Monroe, Adam C. Watts, and Leda N. Kobziar, provides some background information on air quality, the effects of smoke on human health and safety, and regulations concerning the use of prescribed fires and the smoke produced by them, as well as strategies for protecting air quality. Includes links to websites with further information. Published by the UF School of Forest Resources and Conservation, February 2009.